A method for preparing a flexible electrode based on a graphene film with a thickness of only a single carbon atom layer

By spin-coating and etching the graphene film on the mica sheet, the transfer problem of graphene on the non-metallic substrate is solved, and a flexible electrode with high conductivity and high transparency is prepared, suitable for wearable electronic products and flexible electronic devices are realized Widely used.

CN118983145BActive Publication Date: 2025-01-07WENZHOU MEDICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411472828.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-07
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

Traditional graphene is difficult to transfer to non-metallic substrates on metal substrates, affecting the ductility and tensile capabilities of flexible electrodes. The transparency and light transmittance of traditional flexible substrates are insufficient, limiting the development of flexible electronic products.

Method used

Using high-temperature resistant mica sheets as substrates, the graphene film is transferred to the mica sheets by spin coating and etching process, and the graphene film with a single carbon atom layer thickness is prepared by heat treatment and removal of the PMMA protective film. electrode.

Benefits of technology

It achieves flexible electrodes with high conductivity, flexibility and transparency, suitable for wearable electronic products, has excellent stretchability and bending performance, and expands the application range of flexible electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118983145B_ABST
    Figure CN118983145B_ABST
Patent Text Reader

Abstract

A method for preparing a flexible electrode based on a graphene film with a thickness of only a single carbon atom layer comprises the following steps: (1) selecting a mica sheet that is resistant to high temperature, transparent and has good flexibility as an experimental substrate: firstly dissociating the mica sheet until it is flexible enough to be bent multiple times, and then placing it in an ethanol solution for ultrasonic cleaning to obtain a surface of the mica sheet substrate; (2) using a spin coating method to spin-coat PMMA on a graphene layer adhered to a copper foil: fixing the copper foil covered with a graphene layer on a glass slide with tape, and then placing it on a sample stage and fixing it with a vacuum pump, dripping a PMMA solution on the sample and starting a coating machine, the sample rotates at a set speed, and this operation process is repeated twice before drying the sample; (3) after drying, placing the entire copper foil coated with PMMA in a 0.5-3 mol / L / 0.1-2 mol / L FeCl2 / HCL solution for etching, waiting for the copper to gradually dissolve, and when the copper is completely etched away, using a silicon wafer to pick up the graphene film in the solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a flexible electrode based on a graphene film with a thickness of only a single carbon atom layer, and belongs to the field of graphene. Background Art

[0002] With the increasing demand for stretchable, wearable and other flexible electronic products, electrodes are gradually becoming a research hotspot in the industry as an indispensable key component of future flexible electronic products. Since the rigid electrodes in traditional electronic products will no longer meet the development requirements of flexible electronic products due to their inability to bend and lack of flexibility, in addition to good conductivity, good flexibility and ductility are a key point in future electrode design. An ideal flexible electrode needs to meet the following conditions: high conductivity, high stretchability, stable electrochemical properties, high safety and low cost. Many literatures show that the selection of flexible electrode materials is a key factor affecting electrode performance. Considering that graphene has excellent conductivity, light transmittance, thermal conductivity and mechanical properties, and has demonstrated great application value in the fields of electronics and optics. This project aims to develop a flexible transparent electrode with high conductivity and high light transmittance based on graphene.

[0003] However, graphene currently grown on metal substrates cannot generally be used directly and needs to be transferred to a non-metallic target substrate for subsequent applications. The choice of target substrate will seriously affect the extension and stretching ability of flexible electrodes, which is still a difficult problem in the development of flexible electronic products. The choice of traditional flexible substrates is generally concentrated on polymer substrates, such as PET, PI, PMMA, etc., but the growth temperature of such substrates cannot be too high, and the transparency and transmittance are not particularly ideal, which limits their application. Therefore, finding a flexible substrate that is both high temperature resistant and transparent is an urgent problem that needs to be solved in the process of designing flexible electrodes based on graphene films. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a flexible electrode based on a graphene film with a thickness of only a single carbon atomic layer.

[0005] A method for preparing a flexible electrode based on a graphene film with a thickness of only a single carbon atomic layer comprises the following steps:

[0006] (1) Selecting a high temperature resistant, transparent, and flexible mica sheet as the experimental substrate: first dissociate the mica sheet until it is flexible enough to be bent multiple times, and then put it into an ethanol solution for ultrasonic cleaning to obtain the mica sheet substrate surface;

[0007] (2) Use the spin coating method to spin-coat PMMA onto the graphene layer adhered to the copper foil: fix the copper foil covered with the graphene layer on a glass slide with tape, then place it on the sample stage and fix it with a vacuum pump. After dropping PMMA solution on the sample, start the coating machine, and the sample rotates at the set speed. Repeat this operation twice and then dry the sample.

[0008] (3) After drying, the copper foil with PMMA spin-coated on it is placed in a 0.5~3mol / L / 0.1~2mol / L FeCl2 / HCL solution for etching. The copper is gradually dissolved. When the copper is completely etched away, an ultra-thin graphene film can be seen in the solution. The graphene film is picked up with a silicon wafer and placed in a petri dish filled with deionized water for washing.

[0009] (4) Use a syringe to drain the deionized water in the culture dish, and then inject new deionized water for washing. After repeated several times, a layer of ultra-thin graphene film (only a single carbon atom layer thick) can be seen floating in the clean deionized water;

[0010] (5) Use tweezers to hold the mica sheet and pick up the graphene film in the deionized water, and place it on a hot plate for drying;

[0011] (6) placing the graphene-coated mica sheet in an acetone solution with a mass fraction of 80-99.5% and heating and soaking it, repeating the operation three times to remove PMMA;

[0012] (7) The mica sheet with PMMA removed was rinsed in deionized water for multiple times and allowed to dry naturally to obtain a transparent flexible electrode.

[0013] With high temperature resistant mica sheets as substrate, transparent flexible electrodes based on graphene conductive films have good conductivity, flexibility and reliability. The electrode has a simple structure, low cost, thinness and flexibility, and is very suitable for the needs of wearable electronic products. It has broad application prospects in the application of flexible electronic devices. Graphene film exists in a single layer of carbon atoms, so it has extremely excellent stretchability, bending and ductility. Coupled with its excellent conductivity, it can be used as an efficient flexible electrode material to improve the electronic conduction ability of the electrode. Using mica sheets as electrode substrates makes the final electrode have good flexibility and high transparency, and can adapt to flexible devices of various shapes and surfaces, expanding its application range.

[0014] Preferably, in step (2), a dropper with a pore size of about 0.4 μm is used to drop a drop of organic solution PMMA, about 50 ug, on the sample, and then the homogenizer is started.

[0015] By using a dropper with a pore size of about 0.4μm, the amount of PMMA solution added (50μg) can be accurately controlled to ensure the uniformity and thickness of the film layer, making the subsequent spin coating process more consistent. An appropriate amount of PMMA solution can effectively cover the graphene layer and form a high-quality protective film, ensuring that the graphene is not damaged in subsequent processes and improving the integrity and performance of the graphene. After the drop is added, the uniform speed of the glue spreader is started, and the PMMA solution can be evenly coated on the graphene surface through centrifugal force to form a uniform film layer, avoiding the phenomenon of uneven film thickness and improving the reliability of subsequent processing. The uniform PMMA film layer helps the subsequent heat treatment and etching process, ensures the integrity of the graphene layer structure, and improves the performance of the final electrode.

[0016] Furthermore, in step (2), the speed of the glue homogenizer is set as follows: first, the starting gear is set to 500 rpm, and the rotation time is 5 s; then it is set to 1500 rpm, and the rotation time is 5 s; then the speed is adjusted to 4000 rpm, and the rotation time is 25 s; then it is adjusted to 1500 rpm, and the rotation time is 5 s; and finally, it is adjusted to 600 rpm, and the rotation time is 5 s.

[0017] By gradually increasing the rotation speed, the PMMA solution can be evenly distributed on the graphene layer, avoiding bubbles or uneven film thickness, and ensuring the formation of a protective film with good consistency. The first stage at a lower rotation speed (such as 500 rpm) can ensure that PMMA is in better contact with the surface of the graphene layer, which helps to improve the adhesion between the two and reduce the risk of film peeling. At a higher rotation speed (such as 4000 rpm), the centrifugal force during the coating process can effectively accelerate the volatilization of the solvent, promote the rapid drying of the film, and help improve the mechanical stability of the film. Gradually reducing the rotation speed (such as 600 rpm) allows the film layer to have better control over the residual solvent during the drying process, avoiding the impact of solvent residue on electrode performance during subsequent processing.

[0018] Different speed configurations can optimize the structure of the membrane layer, improve the density of the membrane, reduce pores or defects, and thus improve the electrical properties and chemical stability of the electrode. It also improves the repeatability of the operation, making the membrane characteristics more stable during each operation, thereby reducing production fluctuations.

[0019] Preferably, in step (2), the sample is placed on a hot plate and baked at a temperature of 120° C. for 5 minutes.

[0020] Under this temperature and time condition, the residual solvent in the PMMA film can be effectively volatilized, reducing the residual substances in the film layer, thereby preventing the impact on subsequent processes and electrode performance. Heat treatment further increases the adhesion between PMMA and the graphene layer, ensuring the stability of the film layer in subsequent processing and reducing the risk of peeling. Through thermal baking, the PMMA film undergoes a cross-linking reaction at a certain temperature, which helps to improve the density and structural integrity of the film, making it more uniform and strong. The increase in temperature can promote the molecular movement of PMMA, soften it to a certain extent, and enhance the fluidity of the film layer, thereby improving the uniformity and surface smoothness of the film.

[0021] High temperature can greatly accelerate the drying process of the film, shorten the preparation cycle, improve production efficiency, and meet the needs of industrial applications. A reasonable combination of temperature and time can enable PMMA to reach a certain hardness while reducing the transition effect in time, thereby improving the mechanical strength of the film. This temperature and time condition makes the film layer more consistent in physical and chemical properties, laying a good foundation for subsequent etching and reprocessing, and ensuring the smooth progress of the overall process. Through proper temperature control, defects such as bubbles and cracks inside the film can be significantly reduced, the quality of the film can be improved, and its reliability in application can be ensured.

[0022] Preferably, in step (5), the sample is placed on a hot plate and baked at a temperature of 80° C. for 20 min, and then the temperature is raised to 120-150° C. and baked for 20 min, so as to further firmly bond the graphene to the mica substrate.

[0023] Baking at a lower temperature (80°C) helps to gently remove moisture and bubbles that may exist between graphene and the mica substrate, improving the contact and bonding between the two. By raising the temperature to 120-150°C, the molecular movement between graphene and mica sheets can be accelerated, further enhancing the interfacial bonding force, making graphene more firmly attached to the substrate and reducing the risk of peeling. High-temperature baking will promote the densification of the graphene layer and reduce the pores in the film layer, thereby improving its conductivity and mechanical stability. Exposing the sample to a suitable thermal environment can improve the thermal adaptability of the material and provide reliable performance guarantee for graphene in subsequent integrated applications. Enhanced adhesion and density will help maintain excellent electrode performance after long-term use and reduce functional loss caused by interfacial peeling.

[0024] Preferably, in step (6), the heating temperature is 40° C. and the soaking time is 20 min.

[0025] Low temperature immersion helps to improve the solubility of PMMA without damaging the graphene or mica sheets, thereby effectively removing the PMMA protective film and maintaining the integrity of the underlying material. By controlling the temperature at 40°C, the dissolution rate of PMMA can be slowed down, avoiding the impact caused by strong solvents, thereby reducing the risk of damage to the structure and ensuring the stability of the graphene layer during the removal process. Low temperature conditions can minimize thermal stress, so that thermal expansion or contraction of the material will not be triggered during the immersion process, avoiding cracking or deformation of the film. Since the immersion time reaches 20 minutes, it is enough time to ensure that PMMA is completely dissolved, thereby improving the removal effect and reducing residues in subsequent processing.

[0026] The beneficial effects of the present invention are as follows: With high temperature resistant mica sheets as substrates, transparent flexible electrodes based on graphene conductive films have good conductivity, flexibility and reliability. The electrode has a simple structure, low cost, is thin and flexible, and is very suitable for the needs of wearable electronic products, and has broad application prospects in the application of flexible electronic devices. The graphene film exists in a single layer of carbon atomic layer thickness and has excellent electrical conductivity. It can be used as an efficient electrode material to improve the electronic conduction ability of the electrode. Using mica sheets as substrates makes the final electrode have good flexibility and high transparency, and can adapt to flexible devices of various shapes and surfaces, expanding its application range. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0028] Figure 1 It is a mica sheet that can be bent repeatedly after dissociation;

[0029] Figure 2 This is the copper foil sample just put into FeCl2 / HCL solution;

[0030] Figure 3 This is the sample film after copper is completely dissolved;

[0031] Figure 4 A graphene film floating in deionized water;

[0032] Figure 5 A transparent flexible electrode in the process of drying;

[0033] Figure 6 is the transmission spectrum of mica sheet / graphene electrode in visible light-infrared light;

[0034] Figure 7 The 2nd and 100th IV test curves of the Graphene / Al2O3 / Al device;

[0035] Figure 8 The IV curve of the device Graphene / Al2O3 / Al after 1000 repetitions with a curvature radius of 6 mm;

[0036] Fig. 9 (a) Retention characteristics and (b) electrical fatigue resistance of the Graphene / Al2O3 / Al device after repeated bending 1000 times with a curvature radius of 6 mm. DETAILED DESCRIPTION

[0037] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0038] It should be noted that all expressions using "first" and "second" in the embodiments of the present invention are for distinguishing two non-identical entities with the same name or non-identical parameters. It can be seen that "first" and "second" are only for the convenience of expression and should not be understood as limitations on the embodiments of the present invention. The subsequent embodiments will not explain this one by one.

[0039] The directions and positions mentioned in the present invention, such as "upper", "lower", "front", "back", "left", "right", "inside", "outside", "top", "bottom", "side", etc., are only for reference to the directions or positions of the drawings. Therefore, the directions and positions used are for explaining and understanding the present invention, but not for limiting the scope of protection of the present invention.

[0040] Example 1

[0041] A method for preparing a flexible electrode based on a graphene film with a thickness of only a single carbon atomic layer comprises the following steps:

[0042] (1) Selecting a high temperature resistant, transparent, and flexible mica sheet as the experimental substrate: first dissociate the mica sheet until it is flexible enough to be bent multiple times, and then put it into an ethanol solution for ultrasonic cleaning to obtain the mica sheet substrate surface;

[0043] (2) Use the spin coating method to spin-coat PMMA onto the graphene layer adhered to the copper foil: fix the copper foil covered with the graphene layer on a glass slide with tape, then place it on the sample stage and fix it with a vacuum pump. After dropping PMMA solution on the sample, start the coating machine, and the sample rotates at the set speed. Repeat this operation twice and then dry the sample.

[0044] The ultra-thin graphene film on the copper substrate was transferred using a wet transfer method.

[0045] Use a dropper with a pore size of about 0.4μm to drop a drop of organic solution PMMA, about 50ug, on the sample, and then start the homogenizer.

[0046] The speed of the glue homogenizer is set as follows: first set the starting gear to 500rpm, the rotation time is 5s; then set it to 1500rpm, the rotation time is 5s; then adjust the speed to 4000rpm, the rotation time is 25s; then adjust it to 1500rpm, the rotation time is 5s; finally adjust it to 600rpm, the rotation time is 5s.

[0047] The baking temperature is 120°C and the baking time is 5 minutes.

[0048] (3) After drying, the copper foil with PMMA spin-coated was placed in a 0.5 mol / L / 0.1 mol / L FeCl2 / HCL solution for etching. The copper was gradually dissolved. When the copper was completely etched away, an ultra-thin graphene film was visible in the solution. The graphene film was picked up with a silicon wafer and placed in a petri dish filled with deionized water for washing.

[0049] (4) Use a syringe to drain the deionized water in the culture dish, and then inject new deionized water for washing. After repeated several times, a layer of ultra-thin graphene film (only a single carbon atom layer thick) can be seen floating in the clean deionized water;

[0050] (5) Use tweezers to hold the mica sheet and pick up the graphene film in the deionized water, and place it on a hot plate for drying;

[0051] The baking temperature is 80° C. for 20 minutes, and then the temperature is raised to 120° C. for 20 minutes to further firmly bond the graphene to the mica substrate.

[0052] (6) The graphene-coated mica sheet was placed in an acetone solution with a mass fraction of 80% and heated and soaked. The operation was repeated three times to remove PMMA.

[0053] The heating temperature is 40°C and the soaking time is 20 minutes.

[0054] (7) The mica sheet with PMMA removed was rinsed in deionized water for multiple times and allowed to dry naturally to obtain a transparent flexible electrode.

[0055] With high temperature resistant mica sheets as substrate, transparent flexible electrodes based on graphene conductive films have good conductivity, flexibility and reliability. The electrode has a simple structure, low cost, thinness and flexibility, and is very suitable for the needs of wearable electronic products. It has broad application prospects in the application of flexible electronic devices. Graphene film exists in a single layer of carbon atoms, so it has extremely excellent stretchability, bending and ductility. Coupled with its excellent conductivity, it can be used as an efficient flexible electrode material to improve the electronic conduction ability of the electrode. Using mica sheets as electrode substrates makes the final electrode have good flexibility and high transparency, and can adapt to flexible devices of various shapes and surfaces, expanding its application range.

[0056] Single-layer graphene films are highly transparent and suitable for transparent electronic devices, such as touch screens and transparent conductive films, meeting the dual needs of modern electronic products for visual beauty and functionality. The use of high-temperature resistant mica substrates can not only withstand high temperatures in subsequent processing (such as baking and soaking; such as high-temperature growth of dielectric films on electrodes, etc.), improving the thermal stability of the material, but also meet the current demand for transparent electrodes in flexible electronic device applications. By optimizing the thickness and electrode structure, the performance of electrodes in practical applications can be significantly improved, becoming an important component of electronic devices.

[0057] Example 2

[0058] A method for preparing a flexible electrode based on a graphene film with a thickness of only a single carbon atomic layer comprises the following steps:

[0059] (1) Selecting a high temperature resistant, transparent, and flexible mica sheet as the experimental substrate: first dissociate the mica sheet until it is flexible enough to be bent multiple times, and then put it into an ethanol solution for ultrasonic cleaning to obtain the mica sheet substrate surface;

[0060] (2) Use the spin coating method to spin-coat PMMA onto the graphene layer adhered to the copper foil: fix the copper foil covered with the graphene layer on a glass slide with tape, then place it on the sample stage and fix it with a vacuum pump. After dropping PMMA solution on the sample, start the coating machine, and the sample rotates at the set speed. Repeat this operation twice and then dry the sample.

[0061] Use a dropper with a pore size of about 0.4μm to drop a drop of organic solution PMMA, about 50ug, on the sample, and then start the homogenizer.

[0062] The speed of the glue homogenizer is set as follows: first set the starting gear to 500rpm, the rotation time is 5s; then set it to 1500rpm, the rotation time is 5s; then adjust the speed to 4000rpm, the rotation time is 25s; then adjust it to 1500rpm, the rotation time is 5s; finally adjust it to 600rpm, the rotation time is 5s.

[0063] The baking temperature is 120°C and the baking time is 5 minutes.

[0064] (3) After drying, the copper foil with PMMA spin-coated on it was placed in a 1.5 mol / L / 1 mol / L FeCl2 / HCL solution for etching. The copper was gradually dissolved. When the copper was completely etched away, an ultra-thin graphene film was visible in the solution. The graphene film was picked up with a silicon wafer and placed in a petri dish filled with deionized water for washing.

[0065] (4) Use a syringe to drain the deionized water in the culture dish, and then inject new deionized water for washing. After repeated several times, a layer of ultra-thin graphene film (only a single carbon atom layer thick) can be seen floating in the clean deionized water;

[0066] (5) Use tweezers to hold the mica sheet and pick up the graphene film in the deionized water, and place it on a hot plate for drying;

[0067] The baking temperature is 80° C. for 20 minutes, and then the temperature is raised to 135° C. for 20 minutes to further firmly bond the graphene to the mica substrate.

[0068] (6) The graphene-coated mica sheet was placed in a 90% by mass acetone solution for heating and soaking, and the operation was repeated three times to remove PMMA;

[0069] The heating temperature is 40°C and the soaking time is 20 minutes.

[0070] (7) The mica sheet with PMMA removed was rinsed in deionized water for multiple times and allowed to dry naturally to obtain a transparent flexible electrode.

[0071] Example 3

[0072] A method for preparing a flexible electrode based on a graphene film with a thickness of only a single carbon atomic layer comprises the following steps:

[0073] (1) Selecting a high temperature resistant, transparent, and flexible mica sheet as the experimental substrate: first dissociate the mica sheet until it is flexible enough to be bent multiple times, and then put it into an ethanol solution for ultrasonic cleaning to obtain the mica sheet substrate surface;

[0074] (2) Use the spin coating method to spin-coat PMMA onto the graphene layer adhered to the copper foil: fix the copper foil covered with the graphene layer on a glass slide with tape, then place it on the sample stage and fix it with a vacuum pump. After dropping PMMA solution on the sample, start the coating machine, and the sample rotates at the set speed. Repeat this operation twice and then dry the sample.

[0075] Use a dropper with a pore size of about 0.4μm to drop a drop of organic solution PMMA, about 50ug, on the sample, and then start the homogenizer.

[0076] The speed of the glue homogenizer is set as follows: first set the starting gear to 500rpm, the rotation time is 5s; then set it to 1500rpm, the rotation time is 5s; then adjust the speed to 4000rpm, the rotation time is 25s; then adjust it to 1500rpm, the rotation time is 5s; finally adjust it to 600rpm, the rotation time is 5s.

[0077] The baking temperature is 120°C and the baking time is 5 minutes.

[0078] (3) After drying, the copper foil with PMMA spin-coated on it was placed in a 3 mol / L / 2 mol / L FeCl2 / HCL solution for etching. The copper was gradually dissolved. When the copper was completely etched away, an ultra-thin graphene film was visible in the solution. The graphene film was picked up with a silicon wafer and placed in a petri dish filled with deionized water for washing.

[0079] (4) Use a syringe to drain the deionized water in the culture dish, and then inject new deionized water for washing. After repeated several times, a layer of ultra-thin graphene film (only a single carbon atom layer thick) can be seen floating in the clean deionized water;

[0080] (5) Use tweezers to hold the mica sheet and pick up the graphene film in the deionized water, and place it on a hot plate for drying;

[0081] The baking temperature is 80° C. for 20 minutes, and then the temperature is raised to 150° C. for 20 minutes to further firmly bond the graphene to the mica substrate.

[0082] (6) The graphene-coated mica sheet was placed in a 99.5% by mass acetone solution for heating and soaking. The operation was repeated three times to remove PMMA.

[0083] The heating temperature is 40°C and the soaking time is 20 minutes.

[0084] (7) The mica sheet with PMMA removed was rinsed in deionized water for multiple times and allowed to dry naturally to obtain a transparent flexible electrode.

[0085] Electrode characteristics verification:

[0086] Figure 6This is the transmission spectrum of the transparent flexible electrode obtained by successfully transferring the graphene film to the mica sheet in the visible light-infrared light band. As can be seen from the figure, in the visible light range, the transmittance of the electrode is greater than 80% on average, and in the infrared band, although the transmittance decreases, it remains above 70%. It can be seen that the sample has good transmittance. In addition, the resistivity of the electrode measured by the four-probe method is 0.305Ω / cm on average, which is very suitable for electrode applications.

[0087] In order to further verify the performance of the flexible electrode, three quarters of the graphene layer was covered with aluminum foil, and a layer of aluminum was grown on the exposed quarter of the graphene bottom electrode using electron thermal evaporation technology as the lead-out electrode of the bottom electrode. This is to protect the graphene film bottom electrode with a thickness of only a single carbon atom layer (about 0.35nm) from being punctured when contacting the probe. Then, the quarter of the lead-out electrode was covered with aluminum foil, while three quarters of the graphene bottom electrode was exposed. Al2O3 film was grown on the graphene electrode using the ALD method, and Al was prepared as the top electrode using a mask and electron thermal evaporation technology to obtain the corresponding flexible resistive memory device, whose storage structure is Graphene / Al2O3 / Al.

[0088] Figure 7 This is an IV test of the graphene / Al2O3 / Al structure resistive memory device. When conducting electrical tests, the current limit of each device is set to 1mA. Figure 8 It can be seen that except for the first electrical initialization process, the Set voltage of the device is relatively large. After the device completes the initialization process, the second DC scanning curve and the 100th scanning curve of the device do not change much, which shows that the device has good repeatability. The Set voltage of the device fluctuates between 1.5~2V, and the Reset voltage is between -1.1~-1.5V.

[0089] Whether the flexible resistive memory device can maintain its good resistive performance after being subjected to various mechanical bending and repeated bending is the primary indicator for judging the quality of the flexible resistive memory device. Therefore, the device's resistance to mechanical bending will be tested by repeated bending with a radius of 6mm. In the specific operation, the Graphene / Al2O3 / Al device is unfolded and glued to a semi-cylindrical quartz boat with a radius of 6mm, so that the device is bent with a curvature radius of 6mm. After repeated bending 1000 times, the DC scanning test circuit voltage characteristics is carried out. Figure 8 It shows that the resistance characteristics of the device do not change much after repeated mechanical bending with a curvature radius of 6mm for 1000 times. Afterwards, the device was tested for electrical fatigue resistance and data retention characteristics.

[0090] Fig. 9This is a test of the device's retention characteristics and electrical fatigue resistance after 1000 repeated mechanical bending. Fig. 9 (a) It can be seen that the device can maintain a retention time of 1.5*104s in a high temperature environment of 85℃, which shows good retention characteristics and thermal stability. The current storage window ratio corresponding to high and low resistance is stable at 102. Fig. 9 (b) shows that after repeated mechanical bending for 1000 times, the device can still maintain excellent electrical fatigue resistance. During the 100-cycle erase and write process, although the current value corresponding to high resistance has a larger fluctuation relative to low resistance, the current storage window ratio corresponding to high and low resistance is basically stable at 102, which is sufficient to distinguish the "1" and "0" states of the device in practical applications.

[0091] In summary, the electrode has good electrical conductivity and transmittance. In order to further verify the practicality of the flexible electrode, a flexible resistive random access memory with a graphene / Al2O3 / Al structure was prepared. When the flexible transparent electrode is the lower electrode, the storage unit has good repeatability, and the IV resistive random access curve is basically unaffected by repeated bending 1000 times with a curvature radius of 6mm, and can maintain 1.5*104s without failure at a high temperature of 85°C, and can maintain a relatively stable high and low resistance ratio after 100 repeated erasures. The good conductivity, flexibility and reliability of the graphene electrode are fully verified.

[0092] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

[0093] Although the invention has been described with reference to several specific embodiments, it should be understood that the invention is not limited to the specific embodiments disclosed. The invention is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.

Claims

1. A method for preparing a flexible electrode based on a graphene film with a thickness of only a single carbon atom layer, characterized in that: The steps include: (1) Selecting a high temperature resistant, transparent, and flexible mica sheet as the experimental substrate: first dissociate the mica sheet until it is flexible enough to be bent multiple times, and then put it into an ethanol solution for ultrasonic cleaning to obtain the mica sheet substrate surface; (2) Use the spin coating method to spin-coat PMMA onto the graphene layer adhered to the copper foil: fix the copper foil covered with the graphene layer on a glass slide with tape, then place it on the sample stage and fix it with a vacuum pump. After dropping PMMA solution on the sample, start the coating machine, and the sample rotates at the set speed. Repeat this operation twice and then dry the sample. (3) After drying, the copper foil with PMMA spin-coated on it is placed in a 0.5~3mol / L / 0.1~2mol / L FeCl2 / HCL solution for etching. The copper is gradually dissolved. When the copper is completely etched away, an ultra-thin graphene film can be seen in the solution. The graphene film is picked up with a silicon wafer and placed in a petri dish filled with deionized water for washing. (4) Use a syringe to drain the deionized water in the culture dish, and then inject new deionized water for washing. After repeated multiple times, an ultra-thin graphene film with a thickness of only a single carbon atom layer can be seen floating in the clean deionized water; (5) Use tweezers to hold the mica sheet and pick up the graphene film in the deionized water, and place it on a hot plate for drying; (6) placing the graphene-coated mica sheet in an acetone solution with a mass fraction of 80-99.5% and heating and soaking it, repeating the operation three times to remove PMMA; (7) The mica sheet with PMMA removed is rinsed in deionized water for multiple times and dried naturally to obtain a transparent flexible electrode; In step (2), the speed of the glue spreader is set as follows: first set the starting gear to 500 rpm, the rotation time is 5 s; then set it to 1500 rpm, the rotation time is 5 s; then the speed is adjusted to 4000 rpm, the rotation time is 25 s; then adjusted to 1500 rpm, the rotation time is 5 s; and finally adjusted to 600 rpm, the rotation time is 5 s.

2. The method for preparing a flexible electrode based on a graphene film having a thickness of only a single carbon atom layer as claimed in claim 1, characterized in that: In step (2), use a dropper with a pore size of about 0.4 μm to drop a drop of organic solution PMMA, about 50 ug, on the sample, and then start the gel coater.

3. The method for preparing a flexible electrode based on a graphene film having a thickness of only a single carbon atom layer as claimed in claim 1, characterized in that: In step (2), the sample was placed on a hot plate and baked at a temperature of 120° C. for 5 min.

4. The method for preparing a flexible electrode based on a graphene film having a thickness of only a single carbon atom layer as claimed in claim 1, characterized in that: In step (5), the sample is placed on a hot plate and baked at a temperature of 80°C for 20 minutes, and then the temperature is raised to 120-150°C and baked for 20 minutes to further firmly bond the graphene to the mica substrate.

5. The method for preparing a flexible electrode based on a graphene film having a thickness of only a single carbon atom layer as claimed in claim 1, characterized in that: In step (6), the heating temperature is 40° C. and the soaking time is 20 min.

Citation Information

Patent Citations

  • Flexible transparent conducting thin film based on graphene sandwich structure and preparation method thereof

    CN104751934A

  • Novel transparent conducting electrode and intelligent light dimming film comprising same

    CN105807450A